ETNOBOTANI TUMBUHAN BERKHASIAT OBAT DI KAWASAN HUTAN DESA BALLA TUMUKA KABUPATEN MAMASA - Tasiklebok, Setiawati; Karim, Faradilah Farid (Prodi Kehutanan Universitas Khairun, 2025)
Abstract People of Balla Tumuka Village, Mamasa Regency have a tradition of traditional medicine using plants originating from forest areas to cure various diseases. The tradition of traditional medicine by the community has been passed down from generation to generation and is supported by natural resources found in the Balla Tumuka Village forest. This study aims to determine the types of medicinal plants and how they are used by the people of Balla Tumuka Village. The research method is descriptive exploratory with in-depth interview data collection techniques on 43 respondents. The results of the study found that there were 17 types of plants used by tje community for treatment, including Ageratum conyzoides, Hyptis capitata, Spatholobus ferrugenus, Agathis dammara and others. The parts of the plant used are leaves, stems, roots, fruit, sap and tubers. The processing method is by boiling, burning, pounding and eating directly. Diseases that can be treated such as cuts, ulcers, diabetes, coughs, cholesterol. Keywords: ethnobotany, Balla Tumuka forest, traditional, medicinal plants.